Numerical analysis of cracking of massive concrete structures : key topics studied in RILEM Technical Committee TC-CMS - Fairbairn, Eduardo M. R. (2014)
This paper presents the main issues that are being discussed on the newly installed RILEM Technical Committee TC-CMS "Thermal Cracking of Massive Concrete Structures". This international committee is establishing a state-of-art report (STAR) on this subject and a significant part of its content directly related with numerical modeling issues. Therefore the presentation of this paper will be devoted to the discussion of key issues related to numerical modeling of the thermal cracking of concrete, establishing a dialogue with the ABMEC and participants of the Mini-Symposium on Concrete Structures community on the progress of TC-CMS.